Electrical and microstructural properties of Nd₂O₃, Gd₂O₃ doped ZnO-V₂O₅-MnO₂-Nb₂O₅ based varistor ceramics - Isa, Nor Hasanah (2018)
The need for fabricating a reliable protection againts high voltage transients material have gained considerable attention in varistor ceramics field. Therefore, in this research, ZnO: Nd3+, Gd3+ at different doping concentration were prepared using solid state method. This research are focuses on the fabrication and electrical characterization of rare earth oxides (REOs) of neodymium (III) oxide (Nd2O3) and gadolinium (III) oxide (Gd2O3) based ZnO ceramics. The aim of this studies are: (i) to study the effects of concentration of Nd, Gd doped in ZnO ceramics on the electrical and microstructural properties, (ii) to investigate the effect of sintering time on the electrical and microstructural properties of Nd, Gd doped in ZnO ceramics, and (iii) to study the effect of temperature degradation on the electrical properties of ceramics. The ceramics were designed according to (97.40−x)ZnO(0.5)V2O5(2) MnO2 (0.1)Nb2O5 (x)REOs where x = 0.01 to 0.05 mol%. The mixed powder was ball milled, pre-sintered at 800 C and pressed by a 3 tonne pressure to form a 15 mm diameter disc with 1 mm thick. The disc were sintered at 900 C for 120 minutes and characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy dispersive X-ray (EDX), densitometer, and current density (J) – electrical field (E) tool. The optimum doped ceramics were subjected to various sintering time from 120 to 210 minutes. The electrical degradation test were conducted on the ceramics that possessed optimum nonlinear α value with state of 0.85 E1mA for 12 hours at various temperature from 80 to 110 C. Cui et al. (2014) and Nahm (2013) reported that the REOs is a donor dopant promote the formation of cation vacancy and create defect which form the barrier. On the first objective, the fabrication of Nd, Gd doped ZnO based varistor ceramics increasing concentration to 0.03 mol% improve the microstructure properties that decreases the lattice parameter c to 5.2060 (Gd), 5.1982 (Nd) Å, increases density to 5.02 (Nd), 5.22 (Gd) g/cm3, and increases the average grain size (D) to 3.54 μm (Nd) and decreases D to 3.56 μm (Gd), improve the electrical properties that increases the barrier height ФB to 0.886 (Nd), 0.849 (Gd) eV, as a consequence increases the nonlinear α value to 9.91 (Nd), 9.94 (Gd), with increases the breakdown voltage (E1mA) value to 88.90 (Nd), 76.07 (Gd) V/mm, but decreases the leakage current density (JL) to 0.45 (Nd), 0.33 (Gd) mA/cm2, which is a potential material for medium voltage application. The further doping to 0.05 mol% deteriorate the electrical properties which decreases ФB to 0.720 (Nd), 0.641 (Gd) eV, as a consequence decreases the nonlinear α value to 7.10 (Nd), 5.86 (Gd), with decreases E1mA to 70.07 (Nd), 73.40 (Gd) V/mm, but increases JL to 0.45 (Nd), 0.59 (Gd) mA/cm2. The prolonged sintering time causes the decreases of nonlinear α and E1mA with increasing JL (Nahm and Shin, 2003). On the second objective, the prolonged sintering time from 120 to 210 minutes increases the lattice parameter c to 5.2156 (Nd), 5.2128 (Gd) Å but decreases the density to 4.74 (Nd), 4.62 (Gd) g/cm3 and decreases D to 2.67 (Nd), 3.19 (Gd) μm except at 180 minutes (Gd) for lattice parameter c, 210 minutes for density (Nd,Gd) and D (Nd). The ФB is decreases to 0.633 (Nd), 0.563 (Gd) eV as a consequence the nonlinear α value is decreases to 5.74 (Nd), 5.10 (Gd) with decreases of E1mA to 64.03 (Nd), 52.10 (Gd) V/mm with increases of JL to 0.54 (Nd), 0.53 (Gd) mA/cm2 with increasing time except at 180 minutes (Nd) for ФB and nonlinear α value, 210 minutes (Nd) for JL value and 210 minutes (Gd) for all electrical parameter. Degradation causes the drastic increment in the JL and reduction of nonlinear α and E1mA (Abdullah et al., 2016). On the third objective, the degraded ZnO based varistor ceramics doped with Nd2O3 possessed the Negative Creep Leakage Current and increases the nonlinear α value to 6.30 with decreases JL to 0.41 mA/cm2 with increasing temperature from 95 to 110 °C, is better than that doped with Gd which possessed the Positive Creep Leakage Current and decreases the nonlinear α value to 3.71 with increases JL to 0.64 mA/cm2 at 110 °C. The minimum and maximum value of nonlinear α value are 5.10 and 9.94, E1mA are 52.10 and 88.90 V/mm, JL are 0.33 and 0.54 mA/cm2, and D are 2.54 and 3.85 μm show the potential of this material limit. An investigation of the J-E characteristics for doped samples exhibited a nonohmicity depending on the REOs inclusions in the ZnO base matrix. The different proportions of the dopant constituents gave rise to different nonlinear α, E1mA, dan JL. The significance of Nd and Gd doping sintered at 120 minutes raised the E1mA and the nonlinear α but lowered JL.